Corrections of Lower Limb Deformities in Patients with Diastrophic Dysplasia - Al Kaissi, Ali (Orthop Surg, 2014)
OBJECTIVE: Accurate understanding of the cause of the underlying pathology in children with diastrophic dysplasia would help in designing targeted management of their locomotion. METHODS: Diastrophic dysplasia was diagnosed in twelve patients (nine girls and three boys; age range 1–14 years), all of whom presented with small stature and apparent short extremities. Club foot (mostly talipes equinovarus) was the most frequent and consistent abnormality. Concomitant abnormalities such as hip flexion contracture, flexion contractures of the knees with excessive valgus deformity and lateral patellar subluxation, were also encountered. Muscle ultrasound and muscle magnetic resonance imaging imaging showed no myopathic changes and muscle biopsies and the respiratory chain were normal. Serum choline kinase and plasma lactate concentrations were normal. RESULTS: Surgical correction of the foot and ankle in patients with diastrophic dysplasia is extremely difficult because of the markedly distorted anatomy. In all of these children, plantigrade foot was achieved along with the improved function of the locomotor system. Mutations of the diastrophic dysplasia sulfate transporter (also known as solute carrier family 26 member 2) were encountered. CONCLUSION: Arthrogryposis multiplex is the usual terminology used to describe the abnormality in infants with multiple contractures. Diligent orthopaedic care should be provided based on an accurate understanding of the associated syndromes in such children.